![$f(x)+f(x+1) \stackrel{1}{=} 3^x+3^{x+1} \stackrel{2}{=} 3^x+3^x\cdot3^1\stackrel{3}{=}3^x+3\cdot3^x\stackrel{4}{=}4\cdot3^x\stackrel{5}{=}4\cdot f(x)](https://tex.z-dn.net/?f=%24f%28x%29%2Bf%28x%2B1%29%20%5Cstackrel%7B1%7D%7B%3D%7D%203%5Ex%2B3%5E%7Bx%2B1%7D%20%5Cstackrel%7B2%7D%7B%3D%7D%203%5Ex%2B3%5Ex%5Ccdot3%5E1%5Cstackrel%7B3%7D%7B%3D%7D3%5Ex%2B3%5Ccdot3%5Ex%5Cstackrel%7B4%7D%7B%3D%7D4%5Ccdot3%5Ex%5Cstackrel%7B5%7D%7B%3D%7D4%5Ccdot%20f%28x%29)
1) Substitution from definition.
2) We use ![$x^{a+b}=x^a\cdot x^b](https://tex.z-dn.net/?f=%24x%5E%7Ba%2Bb%7D%3Dx%5Ea%5Ccdot%20x%5Eb)
3) We are changing the order of 3 and
.
4) We add 1 and 3
and we get ![4\cdot 3^x](https://tex.z-dn.net/?f=4%5Ccdot%203%5Ex)
5) Substitution from definition (but the other way than at the beginning).
Hello!
1 yard = 3 feet
Hope this helps!!
Answer:
3.75x-8.75 or
Step-by-step explanation:
(y -3)^2 = 4y - 12
Expand.
(y-3)(y -3) = 4y - 12
y² - 6y + 9 = 4y - 12
y² - 6y -4y + 9 + 12 = 0
y² - 10y + 21 = 0
Factors are -7y and - 3y
y² - 10y + 21 = 0
y² - 3y - 7y + 21 = 0
y(y - 3) -7(y - 3) = 0
(y - 3)(y - 7) = 0
y-3 = 0 or y - 7 = 0
y = 0 + 3 or y = 0 + 7
y = 3 or 7